The effectiveness of post-exercise sports massage on blood pressure and heart rate in badminton athletes - Kusnadi, Nanang; Nevitaningrum, Nevitaningrum; Hidayat, Cucu; Afif, Ucu Muhamad; Rahmat , Ade (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2025)
Sports massage is a recovery technique designed to reduce muscle tension, enhance blood circulation, and stabilize cardiovascular function. Given the high-intensity intermittent nature of badminton training and the need for rapid cardiovascular recovery, understanding its effects on blood pressure and heart rate is essential for developing evidence-based recovery strategies. This study aimed to examine the effectiveness of post-exercise sports massage on blood pressure and heart rate in badminton athletes. A quasi-experimental approach with a one-group pretest-posttest design was employed. The participants were 25 badminton athletes aged 19 years from Siliwangi University, who underwent 16 post-exercise sports massage sessions, each lasting 30 minutes. Blood pressure and heart rate were measured using a calibrated Omron HEM-7130 digital sphygmomanometer. Data analysis was conducted using SPSS, including descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon signed-rank test at a 5% significance level (α = 0.05). The results revealed significant reductions in systolic blood pressure, diastolic blood pressure, and heart rate across all participants between pretest and posttest measurements (p < 0.001), indicating the consistent benefits of post-exercise sports massage. In conclusion, post-exercise sports massage effectively reduces blood pressure and heart rate in badminton athletes, supporting its use as a physiological recovery strategy. These findings provide practical implications for coaches and sports medicine practitioners in designing evidence-based recovery protocols, and future research should explore optimal massage duration and frequency across different athletic populations.